Performance of Concrete Beams Reinforced with Various Ratios of Hybrid GFRP/Steel Bars - Phan Duy Nguyen; Vu Hiep Dang; Ngoc Anh Vu (Civil Engineering Journal, 2020)
This paper aims to study the flexural behavior of concrete beams reinforced with hybrid combinations of GFRP/steel bars. To this purpose an experimental program was carried out on four concrete beams reinforced with Glass Fiber Reinforced Polymer (GFRP) and twelve hybrid GFRP/steel Reinforced Concrete (RC) beams. Flexural behavior of the tested beams such as stages of response, failure modes, crack patterns, stiffness, toughness and ductility were analyzed. The experimental results showed that depending on GFRP/steel reinforcement configurations, the behavior of hybrid GFRP/steel RC beams undergoes three or four stages, namely: pre-cracking stage; after concrete cracking and before steel yielding; post-yield stage of the steel bar until peak load and failure stage. Totally six failure modes of hybrid RC beams are reported depending on reinforcement rations and configuration. The effect of reinforcement configuration and ratio of GFRP to steel (ρg) on the crack patterns, stiffness, ductility and toughness of hybrid RC beams are significant. Based on the non-linear deformation model, an analytical model has been developed and validated to determine the steel yielding moment and ultimate moment of hybrid GFRP/steel RC beams. It could be seen that the experimental values were in good agreement with the predicted values.